ANALISIS BEBAN KERJA MENTAL KARYAWAN DEPARTEMEN PERENCANAAN PRODUKSI METODE NASA-TLX DI PT. XYZ - Handika Dwiki Nurcahyo; Rian Prasetyo (Jurnal Inkofar, 2023)
The quickly development of the industrial world requires to think hard, especially in the industrial sector as a form of fulfilling a system that can keep up with the accelerating pace of industry today. Employees as a company resource are expected by the company to always pay attention to the conditions of employees to fulfill optimal resources. PT. XYZ with fluctuating customer requests, so it can cause fatigue when demand rises. In the work process, employees in completing work in the production planning department when production planning process problems often occur such as material arrivals not according to estimates, product defects, and late manufacturing drawings. This can lead to work processes piling up at the end and being chased by the timely completion of orders that have been scheduled for delivery it can cause excessive workload when working when complicated constraints occur. This research will be carried out by analyzing the mental workload in the production planning department. The purpose of this study was to find out how much mental workload there is in the production planning department so that a measurement of the mental workload of employees is obtained to be able to find out the amount of workload of employees in the production planning department. The limitations of this study only analyze the mental workload of employees with structural positions in the production planning department. Based on the calculation of the final NASA-TLX score, 13 respondents in the Production Planning Department had an overloaded workload. Based on the calculation of the proposed mental workload improvement, the total score of the old mental workload was 74.102 in the overload category to become a new mental workload of 56.666 in the optimal category with the addition of 4 employees in structural positions.